Differential Pulse Anodic Stripping Voltammetric Determination of Selenium(IV) with A Methylene Blue-Nafion Modified Gold Electrode - Aziz Ramadan, Abdul; Mandil, Hasna; Ozoun, Amer (Asian Journal of Chemistry, 2011)
Differential pulse anodic stripping voltammetric (DPASV) determination of selenium(IV) using a methylene blue-Nafion modified gold electrode (MBNMGE) has been studied. Selenium(IV) was determined in an aqueous HClO4 medium (1.0 M) at an accumulation potential of -240 mV and an accumulation time of 300 s. The potential was then scanned from 0.0 to 1250 mV by differential pulse anodic stripping voltammetry using the auto-scan facility. The peak height was measured at 1030-1060 mV. The calibration graph for Se(IV) under optimized conditions was linear in the range from 1 × 10-8 to 1 × 10-6 mol L-1 (0.79 ng mL-1 to 79 ng mL-1) and was found to obey the equation y = 11.50x + 0.003, where y and x are the peak current (μA) and Se(IV) concentration (μmol L-1 or μM), respectively. The coefficient of determination was R2 = 0.999. The relative standard deviations (RSD) for determination of Se(IV) at the concentration of 1 × 10-8 mol L-1 was 4.2 % (n = 5). The detection limit was 5.0 × 10-9 mol L-1. This method shows that the results for the determination of Se(IV) using methylene blue-Nafion modified gold electrode were more sensitive and accurate than that obtained using vitamin E-Nafion modified gold electrode (VENMGE) about 5 times and about 1000 times using bare gold electrode.